Advances in the Total Synthesis of Aflatoxins - Yang, Liyan; Wang, Zhonglei (Frontiers in Chemistry, 2021)
Aflatoxins, which are produced by Aspergillus flavus, Aspergillus Nomius, and Aspergillus parasiticus, are a group of pentacyclic natural products with difuran and coumarin skeletons. They mainly include aflatoxins B1, B2, G1, G2, M1, and M2. Biologically, aflatoxins are of concern to human health as they can be present as contaminants in food products. The unique skeletons of aflatoxins and their risk to human health have led to the publication of nine remarkable total syntheses (including three asymmetric syntheses) and ten formal total syntheses (including four asymmetric formal syntheses) of aflatoxins in the past 55 years. To better understand the mechanism of the biological activity of aflatoxins and their presence in samples from the food industry, this review summarizes progress in the total synthesis of aflatoxins.